The Production of Non Collagen Protease Enzyme of Pancreatic Gland, Papaya, Pineapple Juice, Oropon and Microbes for Bating Agent in The Technology of Leather Processing - Setiyono (Setiyono); Sujadi (Sujadi); L. M. Yusiati; Jamhari (Jamhari) (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy